The fundamentals of interactive design - Salmond, Michael and Ambrose, Gavin (AVA fundamentals series, 2013)
Ch 1. Interactive design as a discipline. What is interactive design? ; What does an interactive designer do? ; Interview : Darrell Wilkins, creative director ; The design document ; Using new technology ; Case study : Kaiser Chiefs' website ; Project : Create concepts and storyboards -- ch. 2. Ideas, prototypes and experiences. Where do ideas come from? ; Influences and the creative process ; The medium informs the design ; Emotional attachment to the product ; Designing experiences ; Interview : Lydia Swangren, UX designer ; Case study : Multi-platform delivery ; Project : Engage through interactivity -- ch. 3. The industry process. The pitch ; Interview : David Burrows, design consultant ; Art direction and aesthetic ; Case study : WrestleMania viral campaign ; Project : Create a campaign pitch -- ch. 4. Audience, usability and testing. Design for the audience ; Usability in design : rules and principles ; Usability and content ; Usability and visual communication ; Usability testing ; Interview : Trevor May, mobile designer ; Case study : Glastonbury app ; Project : Create an interactive promotion -- ch. 5. Motion graphics and shareable media. Motion and interactivity ; Augmented reality ; Video and motion graphics ; Interview : Krystal Schultheiss, motion graphics developer ; The video production process ; Viral videos ; Social media ; Interview : Steve Smith, senior developer ; Case study : pq-eyewear website ; Project : Create a campaign for a TV series -- ch. 6. Games. Computer games ; Games as an interactive medium ; Interview : Pete Everett, advergame designer ; Case study : Coca-Cola Open the Games ; Project : Create an advergame
https://katalog.adlr.link/Record/0-738467219